Musculoskeletal problems in soccer players: current concepts - Longo, Umile Giuseppe (CIC Edizioni Internazionali, 2012)
Soccer is the most popular sport worldwide, with about 200 million players, both professionals and amateurs. Because of its popularity, it has been often proposed to be able to prevent or cure health problems around the world. Although participation in football leads to significant physical benefits such as improving well-being, extending life expectancy and reducing the likelihood of several major non-communicable diseases, the possibility to incur in soccer injuries must be considered. On average, an elite football player suffers from 1.5–7.6 injuries each 1,000 hours of training and 12–35 injuries each 1000 hours of match. Several risk factors for soccer injuries have been described. The most important of them are the level of play (the risk appears to be higher in professional than amateur players); the exercise load; and the standard of training. The injury prevention program “The 11”, developed with the support of the Federation Internationale de Football Association (FIFA), aims to reduce the impact of intrinsic injury risk factors in soccer, and it has been validated in that sport. A successive modified version of “The 11” (“The 11+”) has been also shown to be effective in preventing injuries in young female soccer players. The FIFA 11+ provided more than 40% of reduction of the risk of injury. Several factors can be related to the risk of injury during sport. Therefore different exercises or factors might have been responsible for efficacy of the FIFA 11+ to prevent injuries. Several improvements have been surely achieved in the last ten years, but further investigation is needed to improve the benefits of playing soccer on human health.